What Makes Students Succeed in Performing Assessment Tasks? Evidences from a Physical Science Class - Fetalvero, Eddie (Romblon State University Research Journal, 2011)
Successful learning is brought about by an interaction of a lot of factors. An important factor is what the learners already possess before a new learning experience begins. This paper presents evidences from a physical science class about the significant learner-related factors that could explain why students are successful or unsuccessful in performing assessment tasks. Self-assessment rubrics of teachers are included as tools in checking the students’ concepts and understanding while assessment and learning are going on simultaneously. It also addresses some important issues in selecting assessment tasks; designing cognitive structures to ensure that learning can occur while students are being assessed; and developing, validating and testing the reliability of rubrics.